การพัฒนาระบบสารสนเทศเพื่อการจัดการสำหรับโรงแรม - เอกชัย ปัญญาเพ็ชร (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
This research aimed at developing management information system and electronic customer relationship management for boutique hotel which Lanna Mantra hotel as a case study. Research methods consisted of studying and collecting old hotel system through in-depth interview of staff and executive. Moreover, the executives were interviewed more about different types of summary report that they need. After that, the data were analyzed and the system was designed. The system was developed by using the MySQL database to collect data. In addition, PHP language was used to retrieve data from database to display on the website. Results from system development found that the system mostly supported the operation of staff in front office section because it was the most important section of the hotel. Staff in this section had to coordinate with other 4 sections which were general management section, housekeeping and buildings section, food and beverage section and vehicles, maintenance and security section. Moreover, the executive can use data from developed system to plan for hotel management by using summary of staff performance appraisal report from each section. Furthermore, hotel staff can use customer’s information from database with electronic customer relationship management (e-CRM) in order to improve suitable services for specific customers. Developed system was used in Lanna Mantra hotel and evaluated the satisfaction of 2 groups of users which were executive and staff. It was found that they had highest satisfaction towards the developed system.